Fisheries education in Malaysia - M., Shariff; Singh, Tarlochan (1987)
The development of fisheries education in Malaysia, from its beginning in 1959, is described. There are presently three vocational schools and two institutes offering fisheries courses and six fishermen training centers. Five universities offer fisheries-related courses but only one, Universiti Pertanian Malaysia, provides degree courses in fisheries. Most employment opportunities are in government agencies. A number of areas in which improvements to the existing fisheries, educational system should be effected are discussed.